Effect of Nattokinase in D-galactose- and Aluminum Chloride-induced Alzheimer’s Disease Model of Rat - TANIKAWA, TAKASHI; YU, JAMES; HSU, KATE; CHEN, SHINDER; ISHII, AYAKO; KITAMURA, MASASHI (In vivo (Athens), 2024)
Alzheimer's disease (AD) is the most common form of dementia worldwide. Nattokinase is a serine protease extracellularly produced by natto, a fermented product of Bacillus subtilis var. natto. In this study, we investigated the therapeutic effects of nattokinase in a rat model of AD induced by aluminum and D-galactose. Forty Wistar rats were randomly divided into four groups: normal, vehicle, and orally administered nattokinase (NK65 and NK130 groups). Except for the normal group, all groups were treated with AlCl and D-galactose for 10 weeks. The NK65 and NK130 groups additionally received 65 mg/kg/day and 130 mg/kg/day nattokinase, respectively. We analyzed β-amyloid levels in the cerebrospinal fluid (CSF), and the spatial reference test was evaluated using the Morris water maze test. After the Morris water maze test, rats of all groups were subjected to micro-computed tomography (μCT) to assess constructional changes in the brain. Aluminum concentration and β-amyloid levels were analyzed by histochemical staining in all brain tissues. Oral administration of nattokinase in the AD rat model increased free-form β-amyloid levels in the CSF and improved aluminum and amyloid plaque accumulation in the brain. Brain μCT images showed enhanced brain volume with fewer constructional changes after treatment with nattokinase. In the behavioral tests, both the escape latency time in the spatial reference test and the time taken to cross the platform area in the spatial probe test improved partially. The results suggest that nattokinase has potential therapeutic applications in the treatment of AD.